PROMOTING ETHICAL VALUES IN THE UNIVERSITY ENVIRONMENT - Daniela JEDER (Association of Social and Educational Innovation, 2020)
The mission of the universities is to build the infrastructure of the social mind, and to provide directions for the evolution of the society, and the promotion and realization of the process of internalizing ethical values are priorities in this particularly complex and important endeavor. The work we propose underlines the importance that must be given to values in order to build an ethical culture in the university environment and the accents that ethical education can put on to eliminate vulnerabilities, to change mindsets, to build benchmarks for normality and to provide support for moral evolution at the social level.